The ex vivo effects of ethanolic extractions of black cumin seed, turmeric root, and Ceylon cinnamon bark on the human gut microbiota - Karley K. Mahalak; Adrienne B. Narrowe; LinShu Liu; Jenni Firrman; Johanna M. S. Lemons; Pieter Van den Abbeele; Aurélien Baudot; Yuanhang Yao; Yanfang Li; Liangli Yu (PLoS ONE, 2025)
Black cumin, turmeric root, and Ceylon cinnamon bark are spices that have been used for both culinary purposes and in traditional medicine practices. These spices are frequently connected with providing antidiabetic, antimicrobial, anti-inflammatory, and gastroprotective properties. However, most studies on potential health effects have not been performed in humans. Since many of the health effect claims relate to gastrointestinal health, we explored the impact of black cumin extract (BCE), turmeric root extract (TRE), and Ceylon cinnamon extract (CCE) on the human gut microbiota ex vivo using the SIFR ® technology. The impact on the gut microbiota were determined using shotgun sequencing and flow cytometry, while the health-related short-chain fatty acids (SCFA) were analyzed to assess the metabolic output. While TRE and CCE had very little effect on the gut microbiota, BCE significantly increased acetate (+ 8.7mM), butyrate (+1.3mM), and propionate (+3mM) production. This related to specific increases of Alistipes onderdonkii , Alistipes shahii and particularly Candidatus Cibiobacter qucibialis , CCE and TRE increased the health related Faecalibacterium prausnitzii and Dysosmobacter welbionis , respectively, with CCE also increasing Enterococcus and Veillonella species. Overall, these findings indicate these spices may have an impact on the human gut microbiome that could explain their purported health effects.